Community Empowerment, Adult Education and Social Media Approaches to the Opioid Crisis in Vancouver - Griffin, Denneisha T.; Walter, Pierre (The Canadian Journal for the Study of Adult Education / La revue canadienne pour l’étude de l’éducation des adultes, 2025)
This study focuses on how public health workers, as adult educators, and people with lived experience of drug use in Vancouver’s Downtown Eastside create supportive environments and educational programs that foster harm reduction and community empowerment to address the Opioid Crisis. The study uses community empowerment theory as its conceptual framework, and an interpretive case study sensitized by appreciative inquiry as its methodology. Findings show how adult education by public health workers, community members, allies, and activist users of drugs promotes community empowerment. Findings further detail the role of social media in these efforts, and the barriers and limits to social media’s adoption for public health education among marginalized adults. The study highlights the importance of addressing systemic oppression in adult education programming and building relationships with marginalized people with lived experiences, valuing their knowledge and integrating their voices into the design and running of adult education programs for community empowerment.